Histological Study of European Starling Uropygial Gland (Sturnus vulgaris) - Sadoon, Alaa H. (International Journal of Poultry Science, 2011)
Thirty healthy starling obtained to describe the histological structures of uropygial glands. The gland lies on base of tail over the pyostyle muscle and surrounded by a thin capsule consist of dense connective tissue and devoid by smooth muscle. The glands parenchyma composed of a large number of secretary tubules that filled with fat droplets, the tubules radiate out from the center and end blindly at the capsule of the glands.